2016
DOI: 10.1177/0300060516662404
|View full text |Cite
|
Sign up to set email alerts
|

Association between ATG16L1 gene polymorphism and the risk of Crohn’s disease

Abstract: ObjectiveTo perform a meta-analysis to evaluate studies investigating the association between ATG16L1 gene polymorphism and Crohn’s disease.MethodsPubMed, Embase and Web of Science databases were searched for all studies focusing on the association of ATG16L1 and Crohn’s disease. Combined odds ratios with 95% confidence intervals were calculated for four genetic models (allelic model: G allele versus A allele; additive model: GG versus AA; dominant model: GA + GG versus AA; recessive model: GG versus GA + AA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…As one of the first identified susceptibility loci from GWAS studies, ATG16L1 rs2241880 has since provided conflicting evidence over its inclusion and applicability in the molecular profile of IBD susceptibility. To the best of the authors' knowledge, the last meta‐analysis conducted on this topic was in 2017, 17 and since then several more studies have been reported including those in understudied or minority populations, contributing to the growing literature on the impact of rs2241880 in the pathogenesis of IBD. Thus, we sought to provide an updated, comprehensive meta‐analysis of the available literature on ATG16L1 rs2241880 on IBD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the first identified susceptibility loci from GWAS studies, ATG16L1 rs2241880 has since provided conflicting evidence over its inclusion and applicability in the molecular profile of IBD susceptibility. To the best of the authors' knowledge, the last meta‐analysis conducted on this topic was in 2017, 17 and since then several more studies have been reported including those in understudied or minority populations, contributing to the growing literature on the impact of rs2241880 in the pathogenesis of IBD. Thus, we sought to provide an updated, comprehensive meta‐analysis of the available literature on ATG16L1 rs2241880 on IBD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Consequently, autophagy, one of the principal mechanisms by which the host can maintain intestinal homeostasis, both immunologically and microbially, is defective and potentially contributes to IBD pathogenesis. 15 Previous meta-analyses 16,17 have been published on the matter; however, these have generally only focussed on an association with CD susceptibility. What we present here, thus, is the most comprehensive meta-analysis to date on the association of ATG16L1 rs2241880 and IBD, including both CD and UC, determining any relevant demographic susceptibility patterns based on age (paediatric vs. adult), ethnicity (Caucasian, East Asian, South Asian, Middle Eastern, Latin American), and geographical origin (Northern Europe, presence of perianal disease and presence of extraintestinal manifestations (EIM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e ATG16L1 gene is mainly expressed in the colon, small intestine, intestinal epithelial cells, and lymphocytes, and its encoded protein can participate in the metabolism of intracellular autophagosomes and the immune response induced by intracellular pathogens [24]. e single-nucleotide polymorphisms site in the ATG16L1 gene is highly correlated with CD and is an important risk factor for the pathogenesis of CD [25,26] that can affect intestinal microbes and aggravate the local intestinal inflammatory response in CD [27]. ATG16L1 can also regulate the Nod-dependent cytokine immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphisms of substantial genes such as ATG16L1 , IL-23R gene and fucosyltransferase 2 gene are identified to be relevant to the susceptibility to CD, attributing the success to the massive meta-analyses of CD genome-wide association studies [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Several GWAS studies have demonstrated that SNPs in the immunity-related GTPase family M ( IRGM ) and the deletion polymorphism of the IRGM promoter region are closely related to CD.…”
Section: Host Genomics In CDmentioning
confidence: 99%